2012
DOI: 10.1016/j.jvs.2011.06.107
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after revascularization for advanced popliteal artery entrapment syndrome with segmental arterial occlusion

Abstract: In advanced popliteal entrapment syndrome, longer bypass with superficial femoral artery inflow showed poor long-term graft patency rate. The graft patency rate was excellent in patients whose arterial occlusion was confined to the popliteal artery and treated by popliteal interposition graft with reversed saphenous vein. With these data, we suggest that longer bypass extending beyond the popliteal artery might only be indicated in patients with critical limb ischemia when the extent of disease does not allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…CT angiography (CTA), including multiplanar reformation and 3-D volumerendered reconstructions, is helpful in depicting popliteal vascular changes (vessel deviation, stenosis, occlusion, aneurysm formation) and abnormal musculotendinous structures in the setting of PAES [5,19]. Following revascularization for PAES, CTA is recommended to assess graft patency after an abnormal ultrasound (US) [17]. The use of dynamic CTA has also been proposed for the initial workup of PAES, as images of both lower extremities can be obtained at both rest and plantar flexion in a single examination requiring only one contrast bolus [15].…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Popmentioning
confidence: 99%
See 2 more Smart Citations
“…CT angiography (CTA), including multiplanar reformation and 3-D volumerendered reconstructions, is helpful in depicting popliteal vascular changes (vessel deviation, stenosis, occlusion, aneurysm formation) and abnormal musculotendinous structures in the setting of PAES [5,19]. Following revascularization for PAES, CTA is recommended to assess graft patency after an abnormal ultrasound (US) [17]. The use of dynamic CTA has also been proposed for the initial workup of PAES, as images of both lower extremities can be obtained at both rest and plantar flexion in a single examination requiring only one contrast bolus [15].…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Popmentioning
confidence: 99%
“…This is extremely beneficial in the setting of functional PAES, where lack of an anatomic abnormality limits the sensitivity of cross-sectional modalities like CTA and MRA [18]. In PAES patients treated with popliteal bypass, US duplex Doppler is the first-line modality of choice in assessing graft patency; CTA, MRA, and selective arteriography are reserved for postoperative patients with abnormal US duplex Doppler examinations [17].…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Popmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In the report of Kim et al, no patient underwent musculotendinous division alone, owing to late presentation and diagnosis. 14 The authors thus highlighted the need for early referral to a vascular surgeon for early diagnosis and treatment, especially in this population of young patients.…”
Section: Discussionmentioning
confidence: 99%
“…The revascularization procedures consisted of nine interposition procedures with vein grafts and six bypass surgeries with vein grafts. Kim, et al 21) also reported that bypass surgery is associated with a worse patency rate than interposition procedures (5-year, 30.0% versus 85.9%; P = 0.15). Comparing these reports, it can be presumed that short interposition vein grafting has a better patency rate than long bypass vein grafting.…”
Section: Long-term Follow-upmentioning
confidence: 96%